The Gravitational Field and the Dark Energy João Carlos Holland de Barcellos - Holland, João Carlos (IJRDO-Journal of Applied Science, 2016)
The dark energy is a “Ad-Hoc” hypothesis postulated with the only purpose of explaining the apparent fast separation of distant galaxies. The effect observed which indicates a rapid separation is known as “Redshift”. The Redshift of galaxies is currently considered as a Doppler effect of separation. The new theory I will expose explains the Redshift effect with another hypothesis other than the rapid separation of galaxies. With this new hypothesis, the existence of dark energy and dark matter is no longer necessary. In case this theory is confirmed, these “dark” entities may be abandoned permanently. How the idea came to me I was thinking to myself, trying to find a way for the Jocaxian Nothingness (JN) [1] to generate the Aristotelian logic that could explain the apparent ‘logic’ of our universe. I was thinking about what kind of thing the JN would be able to generate in the beginning, but the possibilities were endless… Suppose the JN generates SOMETHING, I thought. This something may or may not have crazy properties, but suppose one of the properties was a restriction to the generation of things inside or outside its limits… While I was day dreaming, all of the SUDDEN I had the idea that the things that are inside the first generated something could decrease in size and the original SOMETHING would remain untouched. If the thing in its interior could decrease in size, the impression given would be that the initial something would be increasing! An expansion! I therefore abandoned my original problem and began to refine this new idea.